N6-Methyladenosine: A Novel RNA Imprint in Human Cancer - Yu, Sihui; Li, Xi; Liu, Shiyun; Yang, Rui; Liu, Xiangnan; Wu, Sufang (Frontiers in Oncology, 2019)
N6-Methyladenosine (m6A), a pervasive posttranscriptional modification which is reversible, has been among hotspot issues in the past several years. The balance of intracellular m6A levels is dynamically maintained by methyltransferase complex and demethylases. Meanwhile, m6A reader proteins specifically recognize modified residues and convey messages so as to set up an efficient and orderly network of m6A regulation. The m6A mark has proved to affect every step of RNA life cycle, from processing in nucleus to translation or degradation in cytoplasm. Subsequently, disorders in m6A methylation are directly related to aberrant RNA metabolism, which results in tumorigenesis and altered drug response. Therefore, uncovering the underlying mechanism of m6A in oncogenic transformation and tumor progression seeks opportunities for novel targets in cancer therapy. In this review, we conclude the extensive impact of m6A on RNA metabolism and highlight its relevance with human cancer, implicating the far-reaching value in clinical application.